Analisis Kerusakan Jalan Kecamatan Buntao Kabupaten Toraja Utara - Hendri Pasongli; Robert Mangontan; Wona Grace Boro (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
The road is the most important transportation facility for the community because it greatly influences their daily activities and activities. Roads are transportation infrastructure capable of providing supporting services in the fields of education, trade, employment and others. Damaged roads are caused by several types of causes, namely vehicles carrying too many goods or excessive loads can cause various problems and the resulting damage is very detrimental to road users. The method used is the Pavement Condition Index (PCI) method with 20 segments and a length of 100 m/segment. Pavement Condition Index (PCI) is a method that gives a rating on the level of road damage from 0 to failed roads and 100 to very good conditions. Based on the calculations, the damage was obtained by means of the Pavement Condition Index method of the many road damages. Severe damage was obtained, namely very poor which had a value of 15 and damage that did not have excellent damage with a value of 100. From the research it was found that the damage was quite severe so that the solution to some of the damage had to be repaired for each type of damage level, from observing the value of the PCI method, then the reconstruction of the handle that is needed is with patches and added layers.